Pope Francis’ Renewal of Pastoral Care in the Logic of Mercy - Hajduk, Ryszard (Studia Warmińskie, 2021)
By showing people mercy, God points to the Church the way to fulfill her saving mission in the world. According to Pope Francis, the renewal of pastoral activity should be carried out in the logic of God’s mercy. As the beating heart of the Gospel, it should be at the center of the message of salvation communicated to people and give shape to pastoral care. The operationalization of the truth about God’s mercy leads pastors to adopt the attitude of going to the periphery of existence, to bring forgiveness and comfort to people wounded by sin, and to be ready to accompany them in achieving full Christian maturity. Their motivation to perform the service in imitation of Jesus Christ, who is the perfect personification of God’s mercy, cannot be weakened by misunderstandings, the disappearance of sin consciousness or a relativistic approach to moral values and principles. Acting in accordance with the logic of mercy, the Church bears witness to her fidelity to God and makes a significant contribution to building a more human world.